INFORMATION CHANGES IN EARNINGS AND CASH FLOWS STOCK PRICES: STUDY OF COMMERCIAL BANKS LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2015-2019 PERIOD) - Inta Budi Setya Nusa (INFOKUM, 2020)
This research was conducted to analyze the effect of information changes in earnings by using net income that has an impact on stock prices and analyzing the effect of information changes in cash flows that have an impact on stock prices. The method used in this study is a descriptive and verification method with a quantitative approach. The Source of data used in this study is secondary data. The population in this study is the annual financial statements of foreign exchange commercial banks listed on the Indonesia Stock Exchange in 2015-2019. The sampling technique in this study was purposive sampling with the number of samples used in this study as many as 65 financial statements from 13 foreign exchange commercial banks during 2015-2019. The statistical test used to test the hypothesis in this study is multiple linear regression, and using SPSS 20.0 software analysis. The results of hypothesis testing in this study indicate that net income has a positive and significant effect on stock prices. While the cash flow variable has a negative and no significant effect on stock prices.